2020
DOI: 10.3390/ijerph17051658
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Longer Working Lives in Europe: Drivers and Barriers in Companies

Abstract: This paper identifies, within companies’ sectors of activity, predictors of Human Resource (HR) policies to extend working life (EWL) in light of increasing policy efforts at the European level to extend working life. Three types of EWL practices are investigated: the prevention of early retirement (i.e., encouraging employees to continue working until the legal retirement age); delay of retirement (i.e., encouraging employees to continue working beyond the legal retirement age); and, recruitment of employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…Several Swedish respondents in this study had access to the early retirement program, and most of them planned to take advantage of it, even though they said they felt healthy enough to continue working longer. Even though parttime retirement seem to have a positive outcome on keeping industrial employees in work beyond retirement age [40], agreements that enable people to stop working earlier may not encourage them to stay longer in the company [16,41]. However, such an agreement will likely be beneficial for the individuals' health as pensioners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Swedish respondents in this study had access to the early retirement program, and most of them planned to take advantage of it, even though they said they felt healthy enough to continue working longer. Even though parttime retirement seem to have a positive outcome on keeping industrial employees in work beyond retirement age [40], agreements that enable people to stop working earlier may not encourage them to stay longer in the company [16,41]. However, such an agreement will likely be beneficial for the individuals' health as pensioners.…”
Section: Discussionmentioning
confidence: 99%
“…However, such an agreement will likely be beneficial for the individuals' health as pensioners. Age management interventions that include individually tailored work, such as part-time retirement, could be strategic to keep older workers and their competence within the company [24,40]. Among the respondents were also people with immigrant backgrounds who had not been living in Sweden long enough to be able to benefit from the local retirement program.…”
Section: Discussionmentioning
confidence: 99%
“…Besides flexible conditions and structures, age management is highlighted by some studies as being essential in promoting EAR (Principi et al 2020). A Swedish qualitative study highlighted the introduction of age management in the workplace as important for retaining older workers (Blomé et al 2018).…”
Section: Scoping 1: Later Life Employmentmentioning
confidence: 99%
“…Within the vast topic of active ageing, two of the presented articles focus on specific aspects of employment in later life. The paper by Andrea Principi and colleagues concerns the management of ageing workers by highlighting the different human resource policies at different companies aimed at lengthening the working lives of older employees [ 5 ]. Using data from a large European study involving companies from six countries, three types of approaches are identified: the prevention of early retirement; the delay of retirement; and the recruitment of employees who are already retired.…”
mentioning
confidence: 99%